2018
DOI: 10.37285/ijpsn.2018.11.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Transmucosal Delivery of Duloxetine Hydrochloride for Prolonged Release: Preparation, in vitro, ex vivo Characteri-zation and in vitro-ex vivo Correlation

Abstract: Duloxetine hydrochloride is a selective serotonin and nor adrenaline reuptake inhibitor. It is used in the treatment of depression, diabetic peripheral neuropathic pain and in moderate to severe stress urinary incontinence in women. However, it undergoes extensive hepatic first-pass metabolism and susceptible to undergo degradation in acidic environment of stomach, which results in the poor bioavailability. The objective of the present study was to develop and evaluate the mucoadhesive buccal tablets (transmuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Abbas et al reported a similar in vitro release profile using the ketotifen in neutral buffer from poly­( n -vinyl-2-pyrrolidone) hydrogel, indicating the erosion and dissolution of hydrogel. Serotonin release followed the Higuchi model, indicating release of biomolecules from an insoluble pectin gel matrix as a square root of a time-dependent process based on Fickian diffusion, and a similar model was reported by Peddapalli et al for drug release kinetics of duloxetine hydrochloride in buccal mucosa at neutral pH. Considerable release of l -tryptophan in SIB occurred within 30 min and followed the Higuchi model, and a similar release model of the same from a hydrogel into neutral phosphate buffer solution has been reported by Larrañeta et al…”
Section: Resultssupporting
confidence: 81%
“…Abbas et al reported a similar in vitro release profile using the ketotifen in neutral buffer from poly­( n -vinyl-2-pyrrolidone) hydrogel, indicating the erosion and dissolution of hydrogel. Serotonin release followed the Higuchi model, indicating release of biomolecules from an insoluble pectin gel matrix as a square root of a time-dependent process based on Fickian diffusion, and a similar model was reported by Peddapalli et al for drug release kinetics of duloxetine hydrochloride in buccal mucosa at neutral pH. Considerable release of l -tryptophan in SIB occurred within 30 min and followed the Higuchi model, and a similar release model of the same from a hydrogel into neutral phosphate buffer solution has been reported by Larrañeta et al…”
Section: Resultssupporting
confidence: 81%
“…Thus, the enhanced and extended absorption of EBT from the oral films might increase the bioavailability. Therefore, transmucosal delivery of EBT through GIT could possibly be enhanced by encapsulating it into transfersomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although DUL shows high oral absorption ( Elsenosy et al, 2020 ), variable poor bioavailability (≈ 40%) is achieved due to the extensive degradation in the acidic medium of the gastrointestinal tract and first-pass metabolism via the hepatic cytochrome P450 P1A2 ( El Sharawy et al, 2017 ; Salem et al, 2022 ). DUL, a BCS class-II drug, is considered a promising candidate for intranasal, as well as transdermal drug delivery, due to its physicochemical properties including lipophilicity (log P = 4.2) and molecular weight (330 g/mol) ( Peddapalli et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various previous trials were conducted to overcome DUL's limitations. El Sharawy et al (2017) , and Peddapalli et al (2018) developed DUL-loaded buccal films and buccal tablets respectively. Setia et al (2013) aimed to surpass the acidic drug degradation by preparing DUL-loaded enteric coated mucoadhesive microspheres.…”
Section: Introductionmentioning
confidence: 99%